2020
DOI: 10.1093/icesjms/fsaa129
|View full text |Cite
|
Sign up to set email alerts
|

Succession in epibenthic communities on artificial reefs associated with marine renewable energy facilities within a tide-swept environment

Abstract: Although colonization of artificial structures by epibenthic communities is well-documented overall, our understanding of colonization processes is largely limited to low-energy environments. In this study, we monitored epibenthic colonization of different structures associated with a tidal energy test site located in a high-energy hydrodynamic environment. Using four years of image-based underwater surveys, we characterized changes through space and time in the taxonomic composition of epibenthic assemblages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…To our knowledge, the single study which had examined the faunal succession of artificial structure colonization in the English Channel were those of Herbert et al (2017) and Taormina et al (2020) [10,51]. Herbert et al (2017) [10] observed different stages in colonisation beginning with bryozoans and green algae which are replaced by red algae, hydroids and ascidians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, the single study which had examined the faunal succession of artificial structure colonization in the English Channel were those of Herbert et al (2017) and Taormina et al (2020) [10,51]. Herbert et al (2017) [10] observed different stages in colonisation beginning with bryozoans and green algae which are replaced by red algae, hydroids and ascidians.…”
Section: Discussionmentioning
confidence: 99%
“…Herbert et al (2017) [10] observed different stages in colonisation beginning with bryozoans and green algae which are replaced by red algae, hydroids and ascidians. Taormina et al (2020) [51] monitored the epibenthic colonization of artificial structures in a subtidal (18-20 m depth) high-energy hydrodynamic environment in the western part of the English Channel at a site planned for the deployment of a tidal turbine. Using four years of image-based underwater studies, they identified a rich fauna (28 taxa) and characterized changes of the epibenthic communities which reached a mature stage at the end of their study.…”
Section: Discussionmentioning
confidence: 99%
“…In part, this is due to the fact that marine habitat surveying is undertaken with a number of different methods and analysis tools, each with different potential sources of error (64,65). In benthic surveys with photo-quadrats and point count analysis, the 'adequate' number of samples (points) per quadrat to accurately describe the community has been a topic of debate (31,(66)(67)(68). The goal is to find a good balance between expert effort (labelling the points in images) and reliability in the derived scene description.…”
Section: Discussionmentioning
confidence: 99%
“…For a long-term (1981-2001) experiment, Nicoletti et al (2007) [14] identified five phases of colonisation for ARs deployed in the mid Tyrrhenian Sea, Italy, from pioneer species during the first months of immersion to Bryozoans bioconstruction dominance at the end of the experiment, and with phase of dominance, regression and absence of the mussel Mytilus galloprovincialis. Recently, Taormina et al (2020) [20] had monitored epibenthic colonization of artificial structure in the subtidal North-Brittany (France) coast using image-based underwater monitorings and showed a mature stage in four years. Finally, our experiment showed the efficiency of such AR on the intertidal zone accessible at each spring tide, which was easier to survey than in the subtidal zone, where divers must be mobilised to sample blocks, and can be easily deployed to test for example different aggregates used in the ARs construction and design.…”
Section: Discussionmentioning
confidence: 99%